The Italo-Abyssinian Crisis and Australian Settler Colonialism in 1935 - Paisley, Fiona (History compass, 2017)
By exploring the themes of settler colonialism and modernity in Australian commentary about Italy's invasion of Abyssinia in 1935, this paper sets out to consider Italy's war in north Africa as an international crisis with significance for Australian progressive narratives about Aboriginal conditions, status and rights important to Australia's international reputation. Thus, Australia's role as a member of the League and a mandatory power will be read in the context of international debate about Italy, modernity, race and violence. My case study draws from the experiences of Bessie Rischbieth, alternate delegate for Australia to the League of Nations in 1935, who observed the Abyssinian protest being made before the Assembly. Rischbieth was seemingly persuaded by Italy's claims to the right to land and territory in the context of immigration restrictions into the United States (and we might add, in relation to Australia) and was provided evidence of slavery in Abyssinia mobilised by Italy and earlier by the Anti-Slavery Society in London in defence of the civilising influence of Europe upon a fellow (non-European) member of the League. However, Rischbieth was also an activist within liberal humanitarian networks critical of Aboriginal policy in Australia in this same era. Her responses to the crisis in African and League affairs offer some insight into the proximities between settler colonialism in Australia and the ‘race’ issues raised by the annexation of Abyssinia by Italy, and its implications for collective security and global governance.